Belarus Public Expenditure and Financial Accountability : Public Financial Management Performance Report - World Bank (Washington, DC, 2014)
The main objective of the present public financial management performance report (PFM-PR) is to provide the Government of Belarus with an objective up-to-date diagnostic of PFM performance based on the internationally recognized public expenditure and financial accountability (PEFA) methodology. The report is expected to inform the development of the government medium-term program for PFM reform. As a lead donor the World Bank provided a qualified team that undertook the assessment in accordance with the methodology and following the process described in the concept note agreed with the ministry of finance (MoF). The World Bank was also responsible for quality assurance of the PFM-PR using the standard procedures for Bank funded analytical work and PEFA check requirements. The report justifies the scoring and describes the analytical work which has been carried out and the sources of information used for each indicator. The report takes into account the changes in PFM performance since 2009 and documents the reasons for changes in indicator scores from the previous assessment. PEFA framework focuses primarily on the national level of a country s PFM system. At the national level it seeks to cover the entire PFM system, including cross-country issues, the revenue side, and the entire budget cycle from planning through execution to control, reporting, and audit. A number of indicators are designed to probe into how the national level interacts with sub-national governments and with public service providers at the local level.